Revising the Communication Mediation Model for a New Political Communication Ecology. (1st October 2017) - Shah, Dhavan V.; McLeod, Douglas M.; Rojas, Hernando; Cho, Jaeho; Wagner, Michael W.; Friedland, Lewis A.
Abstract : A long tradition of research focuses on conversation as a key catalyst for community integration and a focal mediator of media influence on participation. Changes in media systems, political environments, and electoral campaigning demand that these influences, and the communication mediation model, be revised to account for the growing convergence of media and conversation, heightened partisan polarization, and deepening social contentiousness in media politics. We propose a revised communication mediation model that continues to emphasize the centrality of face-to-face and online talk in democratic life, while considering how mediational and self-reflective processes that encourage civic engagement and campaign participation might also erode institutional legitimacy, foster distrust and partisan divergence, disrupting democratic functioning as a consequence of a new communication ecology .